The implications of NATO’s partnership for peace process on European security - Cebeci, Münevver (My University, 1996)
unknown
Keywords: Askerlik bilimi; Karşılıklı güvenlik anlaşmaları; Nato Nort Atlantıc Treaty Organızatıon